2020
DOI: 10.4236/tel.2020.103035
|View full text |Cite
|
Sign up to set email alerts
|

Nexus between Financial Inclusion, Gender and Agriculture Productivity in Ghana

Abstract: The concept of infrastructure, education, availability, usage, affordability, inequality, and accessibility of funds remains useful in agricultural productivity. Nonetheless, the most instrumental challenge of rural farmers is the factors mentioned above, which hindered the growth of agricultural productivity over the years in Africa. As a result, this study examines the nexus between gender, financial inclusion, and Agriculture Productivity in Ghana. The study adopted a cross-sectional research design with se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
4
5
1
Order By: Relevance
“…First, a positive correlation is present between agricultural productivity with carbon dioxide (0.57), labour (0.29), and financial inclusion (0.46). Particularly, the positive relationship between financial inclusion and agricultural productivity (also observed in other studies like Laha, Kuri 2014; Fowowe 2020; Atakli, Agbenyo, 2020) indicates that access to banking services leads to an increase in agricultural productivity in South Asian countries. Second, other explanatory variables like trade openness, physical capital and interest rate are negatively correlated with agricultural productivity.…”
Section: Correlation Matrixsupporting
confidence: 63%
See 2 more Smart Citations
“…First, a positive correlation is present between agricultural productivity with carbon dioxide (0.57), labour (0.29), and financial inclusion (0.46). Particularly, the positive relationship between financial inclusion and agricultural productivity (also observed in other studies like Laha, Kuri 2014; Fowowe 2020; Atakli, Agbenyo, 2020) indicates that access to banking services leads to an increase in agricultural productivity in South Asian countries. Second, other explanatory variables like trade openness, physical capital and interest rate are negatively correlated with agricultural productivity.…”
Section: Correlation Matrixsupporting
confidence: 63%
“…He used simple panel data estimation and his empirical results reveal that FI has a positive influence on agricultural productivity. Atakli, Agbenyo (2020) used Ghana Living Statistical Survey data and multiple regression models. Their results confirm that FI has a positive association with agricultural productivity.…”
Section: Nexus Between Agricultural Finance Financial Inclusion (Fi) ...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, they posited that growth in these channels is hindered by trust and poor documentation issues as well as distance to the nearest financial institution. Irrespective of the measuring yardsticks selected, for Africa and most developing economies, it has been found that the choice of indices to use is heavily influenced by factors such as age, gender, household size, socio-cultural characteristics, education level and internet access [1,[41][42][43] (Zhang and Posso, 2019). The researchers found that despite increases in levels and depth of financial literacy, these factors often significantly influence the decision-making efforts of the vulnerable and financially disadvantaged.…”
Section: The Concept Of Financial Inclusionmentioning
confidence: 99%
“…However, following the revision of the Strategy in 2018 and licensing of new mobile money players, the value of mobile money transactions grew significantly to N5.09 trillion and N9. 43 was as of August 2020 implying that the wallet share is likely to further increase when the full year position is subsequently made available. This therefore underscores the need to continue to develop this subsector as a veritable avenue in pushing the financial inclusion drive.…”
Section: Fig 6 Nigeria Financial Inclusion Growth Trajectorymentioning
confidence: 99%